A Fuzzy-Controlled Comprehensive Learning Particle Swarm Optimizer - Omran, Mahamed G. H.; Clerc, Maurice; Salman, Ayed; Alsharhan, Salah (Swarm Intelligence Based Optimization, 2014)
An adaptive variant of Comprehensive Learning Particle Swarm Optimizer (CLPSO) is proposed in this paper. The proposed method, called Fuzzy-Controlled CLPSO (FC-CLPSO), uses a fuzzy controller to tune the probability learning, inertia weight and acceleration coefficient of each particle in the swarm. The FC-CLPSO is compared with CLPSO and SPSO2011 on 11 benchmark functions. The results show that FC-CLPSO generally outperformed CLPSO and SPSO2011 on most of the tested functions.